Transcriptome Analysis of Salvia miltiorrhiza under Drought Stress - Siwei Zhang; Xinlan Qi; Ruiyan Zhu; Dongdong Ye; Minyu Shou; Lulu Peng; Minghua Qiu; Min Shi; Guoyin Kai (Plants, 2024)
Phenolic acids are one of the major secondary metabolites accumulated in Salvia miltiorrhiza with various pharmacological activities. Moderate drought stress can promote the accumulation of phenolic acids in S. miltiorrhiza, while the mechanism remains unclear. Therefore, we performed transcriptome sequencing of S. miltiorrhiza under drought treatment. A total of 47,169 unigenes were successfully annotated in at least one of the six major databases. Key enzyme genes involved in the phenolic acid biosynthetic pathway, including SmPAL, SmC4H, Sm4CL, SmTAT, SmHPPR, SmRAS and SmCYP98A14, were induced. Unigenes annotated as laccase correlated with SmRAS and SmCYP98A14 were analyzed, and seven candidates that may be involved in the key step of SalB biosynthesis by RA were obtained. A total of 15 transcription factors significantly up-regulated at 2 h and 4 h potentially regulating phenolic acid biosynthesis were screened out. TRINITY_DN14213_c0_g1 (AP2/ERF) significantly transactivated the expression of SmC4H and SmRAS, suggesting its role in the regulation of phenolic acid biosynthesis. GO and KEGG enrichment analysis of differential expression genes showed that phenylpropanoid biosynthesis and plant hormone signal transduction were significantly higher. The ABA-dependent pathway is essential for resistance to drought and phenolic acid accumulation. Expression patterns in drought and ABA databases showed that four PYLs respond to both drought and ABA, and three potential SnRK2 family members were annotated and analyzed. The present study presented a comprehensive transcriptome analysis of S. miltiorrhiza affected by drought, which provides a rich source for understanding the molecular mechanism facing abiotic stress in S. miltiorrhiza.